sPinal coRd stimulatiOn coMpared with lumbar InStrumEntation for low back pain after previous lumbar decompression (PROMISE): a prospective multicentre RCT - Krauss, Philipp Emanuel; Motov, Stefan; Bonk, Maximilian Niklas; Prescher, Andrea; Scorzin, Jasmin; Hajiabadi, Mohammad Mehdi; Schulte, Dirk Michael; Sommer, Bjoern; Seiz-Rosenhagen, Marcel; Ahmadi, Rezvan; Maciaczyk, Jaroslaw; Lehmberg, Jens; et al. (BMJ open, 2023)
Introduction Persistent spine pain syndrome type 2 (PSPS2) represents a significant burden to the individual and society. Treatment options include revision surgery, stabilisation surgery of the spine, neuromodulation, analgesics and cognitive behavioural therapy. Nevertheless, structured treatment algorithms are missing as high-level evidence on the various treatments is sparse. The aim of this study is to compare higher frequency neuromodulation with instrumentation surgery in patients suffering from PSPS2. - Methods and analysis The sPinal coRd stimulatiOn coMpared with lumbar InStrumEntation for low back pain after previous lumbar decompression (PROMISE) trial is a prospective randomised rater blinded multicentre study. Patients suffering from PSPS2 with a functional burden of Oswestry Disability Index (ODI) >20 points are randomised to treatment via spinal cord stimulation or spinal instrumentation. Primary outcome is back-related functional outcome according to the ODI 12 months after treatment. Secondary outcomes include pain perception (visual analogue scale), Short Form-36, EuroQOL5D, the amount of analgesics, the length of periprocedural hospitalisation and adverse events. Follow-up visits are planned at 3 and 12 months after treatment. Patients with previous lumbar instrumentation, symptomatic spinal stenosis, radiographical apparent spinal instability or severe psychiatric or systemic comorbidities are excluded from the study. In order to detect a significant difference of ≥10 points (ODI) with a power of 80%, n=72 patients need to be included. The recruitment period will be 24 months with a subsequent 12 months follow-up. The beginning of enrolment is planned for October 2022. - Ethics and dissemination The PROMISE trial is the first randomised rater blinded multicentre study comparing the functional effectiveness of spinal instrumentation versus neuromodulation in patients with PSPS2 in order to achieve high-level evidence for these commonly used treatment options in this severely disabling condition. Patient recruitment will be performed at regular outpatient clinic visits. No further (print, social media) publicity is planned. The study is approved by the local ethics committee (LMU Munich, Germany) and will be conducted according to the Declaration of Helsinki. - Trial registration number NCT05466110.